Molecular characterization of an inhibitor of NF-κB in the scallop Argopecten purpuratus: First insights into its role on antimicrobial peptide regulation in a mollusk. (May 2016) - Oyanedel, D.; Gonzalez, R.; Flores-Herrera, P.; Brokordt, K.; Rosa, R.D.; Mercado, L.; Schmitt, P.
Abstract: Inhibitors of nuclear factor kappa B (IκBs) are major control components of the Rel/NF-κB signaling pathway, a key regulator in the modulation of the expression of immune-related genes in vertebrates and invertebrates. The activation of the Rel/NF-κB signaling pathway depends largely in the degradation of IκB proteins and thus, IκBs are a main target for the identification of genes whose expression is controlled by Rel/NF-κB pathway. In order to identify such regulation in bivalve mollusks, the cDNA sequence encoding an IκB protein was characterized in the scallop Argopecten purpuratus, Ap IκB. The cDNA sequence of ApIκB is comprised of 1480 nucleotides with a 1086 bp open reading frame encoding for 362 amino acids. Bioinformatics analysis showed that Ap IκB displays the conserved features of IκB proteins. The deduced amino acid sequence consists of a 39.7 kDa protein, which has an N-terminal degradation motif, six ankyrin repeats and a C-terminal phosphorylation site motif. Phylogenetic analysis revealed a high degree of identity between Ap IκB and other IκBs from mollusks, but also to arthropod cactus proteins and vertebrate IκBs. Tissue expression analysis indicated that ApIκB is expressed in all examined tissues and it is upregulated in circulating hemocytes from scallops challenged with the pathogenic Gram-negative bacterium Vibrio splendidus . After inhibiting ApIκB gene expression using the RNA interference technology, the gene expression of the antimicrobial peptide big defensin was upregulated in hemocytes from non-challenged scallops. Results suggest that Ap IκB may control the expression of antimicrobial effectors such as big defensin via a putative Rel/NF-κB signaling pathway. This first evidence will help to deepen the knowledge of the Rel/NF-κB conserved pathway in scallops. Highlights: The sequence encoding an inhibitor of NF-κB was characterized in Argopecten purpuratus . Ap IκB deduced protein sequence displays the conserved features of other IκB proteins. ApIκB mRNA is ubiquitously expressed and it is upregulated in immune challenged scallops. The silencing of ApIκB expression by RNAi causes the upregulation of Big-Defensin. Results suggest a conserved role of ApIκB in regulating Rel/NF-κB in mollusks.